INVESTIGATING PARENTS’ RECOGNITION OF THE NEED FOR ADOLESCENT MENTAL HEALTH SERVICES IN REMOTE AREAS - Isni, Khoiriyah; Pratiwi, Firdha Yovianti; Santri, Ichtiarini Nurullita; Tukiyo, Intan Wahyuni (The Indonesian Journal of Public Health, 2025)
Introduction: The prevalence of depression among children under 15 in Kulon Progo Regency reaches 6%, while emotional and mental disorders affect 8%, with only 9% of affected individuals receiving adequate treatment. Parental behaviour influences the utilisation of mental health services for adolescents, shaping how service needs are assessed. Limited mental health resources and negative parental attitudes further exacerbate adolescent mental health conditions. Aims: This study aims to evaluate parental attitudes toward access to mental health services for adolescents. Method: Using a cross-sectional design, a total of 107 biological parents of adolescents aged 10 to 24 years were selected using purposive sampling. Result: This study finds that perceived severity, perceived threat, and cues to action significantly influence parental behaviour in seeking mental health services (p < 0.05). While 57% of parents reported inappropriate use of services and perceived no benefits from them, 51.4% acknowledged no access barriers. However, only 49.5% demonstrated strong self-efficacy, and 53.3% failed to take timely action. Conclusion: The findings underscore the need for interventions that equip parents with practical knowledge and skills to obtain appropriate mental health services for their adolescent.